KINETIC CHARACTERISTICS OF UP-CONVERSION LUMINESCENCE IN FLUOROPHOSPHATE GLASSES DOPED WITH Tm3+ AND Yb3+ IONS, EXCITED BY CW AND PULSED FEMTOSECOND INFRARED RADIATION - G, Munkhbayar; I.A. Khodasevich; M.V. Korolkov; A.S. Grabtchikov; J. Davaasambuu; D.S. Mogilevtsev; V.A. Dlugunovich; A.V. Isaevich; V.S. Stepura (Scientific transaction of the National University of Mongolia. Physics, 2024)
We report kinetics of rise and decay of up-conversion luminescence in processes involving Tm3+ ions in fluorophosphate glass upon excitation of Yb3+ ions by continuous and pulsed femtosecond radiation. We observe several characteristic times in time-profiles of up-conversion rise and decay fronts. Also, the luminescence decay process with continuous pump behaves in a completely different way in comparison with femtosecond pulsed pump with increasing pump power.